DEVELOPMENT AND VALIDATION OF HPTLC METHOD FOR ESTIMATION OF PRULIFLOXACIN IN FORMULATIONS - DEEPAK POKHARKAR,; RUPESH PINGALE,; SUVARNA PHADATARE,; LAWANYA LATA PANDEY, (International Journal of Pharma and Bio Sciences, 2015)
A new Simple and Rapid high-performance thin-layer chromatographic method was developed and validated for quantitative determination of Pruliflioxacin. Chromatographic separation studies were carried out on prulifloxacin. TLC procedure was optimized with varying ratios of n-propanol, methanol and ammonia. The mobile phase n-propane: methanol: ammonia with ratio (5.1:0.9:0.9 v/v/v) gave good resolution as well as a well defined peak at Rf value of 0.18..The linear regression analysis data for the calibration plots showed a good linear relationship with ð‘Ÿ 2 = 0.9972 in the concentration range 20– 160ng/spot. The method was validated for precision, recovery, repeatability, and robustness as per the International Conference on Harmonization guidelines. Statistical analysis of the data showed that the method is precise, accurate, reproducible, and selected for the analysis of Prulifloxacin. The method is successfully employed in the estimation of equilibrium solubility, quantification of prulifloxacin as a bulk drug, in commercially available preparation.